Are There Linguistic Markers of Suicidal Writing That Can Predict the Course of Treatment? A Repeated Measures Longitudinal Analysis. Issue 3 (2nd July 2016) - Brancu, Mira; Jobes, David; Wagner, Barry M.; Greene, Jeffrey A.; Fratto, Timothy A.
Abstract : The purpose of this pilot study was to predict resolution of suicidal ideation and risk over the course of therapy among suicidal outpatients (N = 144) using a novel method for analyzing Self- verses Relationally oriented qualitative written responses to the Suicide Status Form (SSF). A content analysis software program was used to extract word counts and a repeated measures longitudinal design was implemented to assess improvement over time. Patients with primarily Relationally focused word counts were more likely to have a quicker suicide risk resolution than those with more Self-focused word counts (6–7 sessions versus 17–18 sessions). Implications of these data are discussed, including the potential for enhancing treatment outcomes using this method with individuals entering treatment.